Effects of X-shaped reduction-sensitive amphiphilic block copolymer on drug delivery - Xiao H (Dove Medical Press, 2015)
Haijun Xiao, Lu WangState Key Laboratory of Quality Research in Chinese Medicine, Institute of Chinese Medical Sciences, University of Macau, Macau, People’s Republic of ChinaAbstract: To study the effects of X-shaped amphiphilic block copolymers on delivery of docetaxel (DTX) and the reduction-sensitive property on drug release, a novel reduction-sensitive amphiphilic copolymer, (PLGA)2-SS-4-arm-PEG2000 with a Gemini-like X-shape, was successfully synthesized. The formation of nanomicelles was proved with respect to the blue shift of the emission fluorescence as well as the fluorescent intensity increase of coumarin 6-loaded particles. The X-shaped polymers exhibited a smaller critical micelle concentration value and possessed higher micellar stability in comparison with those of linear ones. The size of X-shaped (PLGA)2-SS-4-arm-PEG2000 polymer nanomicelles (XNMs) was much smaller than that of nanomicelles prepared with linear polymers. The reduction sensitivity of polymers was confirmed by the increase of micellar sizes as well as the in vitro drug release profile of DTX-loaded XNMs (DTX/XNMs). Cytotoxicity assays in vitro revealed that the blank XNMs were nontoxic against A2780 cells up to a concentration of 50 µg/mL, displaying good biocompatibility. DTX/XNMs were more toxic against A2780 cells than other formulations in both dose- and time-dependent manners. Cellular uptake assay displayed a higher intracellular drug delivery efficiency of XNMs than that of nanomicelles prepared with linear polymers. Besides, the promotion of tubulin polymerization induced by DTX was visualized by immunofluorescence analysis, and the acceleration of apoptotic process against A2780 cells was also imaged using a fluorescent staining method. Therefore, this X-shaped reduction-sensitive (PLGA)2-SS-4-arm-PEG2000 copolymer could effectively improve the micellar stability and significantly enhance the therapeutic efficacy of DTX by increasing the cellular uptake and selectively accelerating the drug release inside cancer cells.Keywords: PLGA, 4-arm PEG, micelle, stability, uptake